Transportation and Logistics Networks in the Baltic States: Keys for Successful Economic Development and Integration Into the E.U. - Spens, Karen M.; Kovács, Gyongyi; Vellenga, David B. (Ekonomika, 2004)
This paper aims at reviewing the current state of transport infrastructure in the Baltic States, listing - their main developments and challenges. The interest in the Baltic states originates from two distinct perspectives: their importance as a new market within the EU and their transit function for trade with Russia. Combining these views leads to forecasts of raising trade volumes that the transport infrastructure in the Baltic states must consider. Recent developments, however, point to another direction. In essence, it is questioned how long the Baltic States will be able to function as a gateway for other EU member states to the Russian market. The paper therefore discusses new logistics trends, mainly focusing on the importance of supply chain management (SCM) and a supply chain orientation in providing future opportunities for the transport sector and logistics service providers in the Baltic states.